Study on Practical Quantum-based Security for 6G RAN - Anjar Priyatna; Khoirul Anwar; Gelar Budiman (eProceedings of Engineering, 2026)
Advancements in mobile network technologies have quickly led to the 6G era, increasing data rates and connectivity for future communications. However, implementing quantum security technology to existing devices is not straightforward, particularly in the area of Radio Access Networks (RAN). This paper studies on practical quantum-based security solutions for 6G RAN by exploring three key objectives: (i) analyzing various documents and standards for Quantum Key Distribution (QKD) in International Telecommunication Union (ITU), (ii) analyzing possible infrastructure and fronthaul system model of quantum-based security for 6G RAN, (iii) comparing different QKD protocols in terms of its strengths, weakness, security features and possible applications to identify whether it is possible for integration into 6G infrastructures and (iv) proposed scheme for QKD deployments for Indonesia case study. This paper aims to contribute to the development of a secure, quantumresistant RAN for 6G by incorporating insights from the latest standards in various documents. Index Terms—Quantum Key Distribution, Security, Radio Access Network, Sixth-Generation Wireless Network (6G).